2011
DOI: 10.1155/2011/172965
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Culture Technique Produces Functional Dendritic‐Like Cells from Human Acute Myeloid Leukemia Cell Lines

Abstract: Most anti-cancer immunotherapeutic strategies involving dendritic cells (DC) as vaccines rely upon the adoptive transfer of DC loaded with exogenous tumour-peptides. This study utilized human acute myeloid leukemia (AML) cells as progenitors from which functional dendritic-like antigen presenting cells (DLC) were generated, that constitutively express tumour antigens for recognition by CD8+ T cells. DLC were generated from AML cell lines KG-1 and MUTZ-3 using rapid culture techniques and appropriate cytokines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Consistent with a previous published results [34][35][36][37][38][39][40][41] , we confirmed an increase of csHLADR following TNF and LPS treatment for the monocytic-like cell line MUTZ-3, where both stimulants elicited a response of similar magnitude. This is also consistent with the increase in allogenic T cell-activation potential by induced-MUTZ-3 found by T cell proliferation assays 38 . However, our assessment of total HLA-II abundance by mass spectrometry showed a larger effect in stimulated MUTZ-3 cells, suggesting that an accumulation of HLA-α chain may occur at the intracellular compartments.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with a previous published results [34][35][36][37][38][39][40][41] , we confirmed an increase of csHLADR following TNF and LPS treatment for the monocytic-like cell line MUTZ-3, where both stimulants elicited a response of similar magnitude. This is also consistent with the increase in allogenic T cell-activation potential by induced-MUTZ-3 found by T cell proliferation assays 38 . However, our assessment of total HLA-II abundance by mass spectrometry showed a larger effect in stimulated MUTZ-3 cells, suggesting that an accumulation of HLA-α chain may occur at the intracellular compartments.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, signal transduction upon different maturation signals may be also affected by cell cycle phase and receptor-mediated responses at the single-cell level. Overall, these findings are consistent with the proinflammatory response by MUTZ-3 differentiated into DCs in cytokine production and chemokines as well as the immunophenotypic profile reported, which maturation more closely recapitulates that of DCs [34][35][36]38,41 .We have shown that HLA-DRA1 protein is the most abundant α-chain variant (> 90%), followed by -DPA1 (3-7%) and -DQA1 (< 1%) when detected, irrespective of the HLA-II haplotype in dendritic-cell lines KG-1 and MUTZ-3. This was also observed in monocyte-derived DCs, where HLA-DRA1 levels were consistently higher than -DPA1, and -DPA1 was consistently higher than DQA1.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Priess is a DRB1*04:01-homozygous lymphoblastoid cell line (84). KG-1 is an acute myleloid leukemia cell line (85) with features resembling immature DCs (86,87), expressing DRB1*11 and *14 (88). Cells were grown at 37 ˚C in a humidified incubator, in RPMI1640 medium supplemented with 10% FBS, 2 mM L-glutamine, and penicillin/streptomycin, except for KG-1 cells, which were grown in IMDM with 20% Monocyte-derived dendritic cell culture Monocyte-derived dendritic cells were derived from healthy donor blood as described (45) with modifications as follows.…”
Section: Cell Culture and Inhibitor Studiesmentioning
confidence: 99%
“…In AML, this approach is complicated by the difficulty to generate DCs from every patient [42]. To circumvent this, AML cell lines such as MUTZ-3 [92] and DCOne [93] have been used to generate allogeneic leukemic-DCs. Notably, DCP-001, a novel allogeneic DC vaccine generated from the DCOne AML cell line has shown remarkable results in a cohort of elderly advanced-stage AML patients, with 6/12 patients unexpectedly surviving over 6 months [93].…”
Section: Dc-based Immunotherapy In Leukemiamentioning
confidence: 99%